Multigene phylogenetic and morphological evidence for seven new species of Aquanectria and Gliocladiopsis (Ascomycota, Hypocreales) from tropical areas. (4th March 2019) - Gordillo, Ana; Decock, Cony
ABSTRACT: Aquanectria and Gliocladiopsis are two closely related genera of Hypocreales. They are also morphologically similar, forming hyaline, penicillate conidiophores and hyaline, straight to sinuous, 0–1-septate phialoconidia. During a revision of gliocladiopsis-like isolates originating from rain forest areas of South America (Ecuador, French Guiana) and Southeast Asia (Singapore), multilocus phylogenetic inferences, based on DNA sequences encoding partial β-tubulin ( TUB2 ), translation elongation factor 1-α ( TEF1- α ), histone H3 ( HIS3 ) genes and the nuc rDNA internal transcribed spacer region (ITS1-5.8S-ITS2 = ITS), revealed the occurrence of seven new phylogenetic species. These phylogenetic species also revealed unique combinations of phenotypes, allowing morphological distinction from their closest phylogenetic relatives. Four new species of Aquanectria and three new species of Gliocladiopsis are described and illustrated. Three of the four Aquanectria species deviate from the other species in the genus by having shorter conidia, which are in the size range observed in Gliocladiopsis species. They are placed in Aquanectria based on the phylogenetic analysis, but this also makes the morphological distinction between these two genera obsolete.